Estimating the non-property tangible direct and indirect flood damage : 16th June 2010 flash flood at Orchard Road and potential flash floods at main amenities in Singapore. - Choo, Mei Xuan. (2013)
Occurrence of flash flood in Singapore results in both direct and indirect damages to the economy. On 16th June 2010, the most serious flash flood that occurred at Orchard Road in 26 years has gained public attention on the effectiveness of the water management systems. Benefits derived from the implementations of the flood protection and prevention measures are the flood damages which could have been avoided. Hence, the computations of flood damages are required in the process of conducting cost-benefit analysis. Since there is no previous study conducted to estimate the cost of damages at Orchard Road on 16th June 2010, this study would examine the cost of damages as a case study for the application of cost-benefit analysis. Aspects such as retail businesses losses, traffic disruptions and tourists’ perceptions on the reputation of Orchard Road as a world-renowned shopping district would be focused on. In view of the rapid climate change, potential flash floods at the main amenities such as expressways, schools and airport would also be simulated and indirect cost would be estimated. Our findings show the extent of damage particularly at Lucky Plaza and the total delay and marginal cost due to traffic disruptions at Orchard Road. Furthermore, it is observed that potential flash flood at expressways, schools and Changi Airport for a period of a day or two days would incur substantial economic losses.